Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.32526/ennrj.17.4.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality in Steel Rolling Industries and Possible Health Effects

Abstract: Indoor air quality has significant impacts on occupational health, workers' comfort and their productivity. The aim of this study was to assess indoor air quality in a rolling steel plant and to identify corrective measures that could help improve indoor air quality. Many air quality indicators, namely: CO, CO2, VOCs, NOx, SO2, O3, PM10 and PM2.5 were assessed as part of the study. The results obtained showed that higher concentrations of CO, VOCs, were found at the furnace area, while the rolling and quenchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…They concluded by underlining the need for further research in order to better depict the complicated relationship between IAQ and health interaction symptoms [11]. A research conducted on the effects of indoor air quality on the health of workers in Middle East showed that the first most affected part of workers' bodies is their respiratory system; the second most affected one is their cardiovascular system, and the third most affected one is their visual system [12].…”
Section: Health Problems Associated With Workplace Indoor Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded by underlining the need for further research in order to better depict the complicated relationship between IAQ and health interaction symptoms [11]. A research conducted on the effects of indoor air quality on the health of workers in Middle East showed that the first most affected part of workers' bodies is their respiratory system; the second most affected one is their cardiovascular system, and the third most affected one is their visual system [12].…”
Section: Health Problems Associated With Workplace Indoor Air Pollutionmentioning
confidence: 99%
“…As a result, global warming caused by greenhouse effect has become a very important public problem. The rate of carbon dioxide in today's air is around 390 ppm and it increases by 2 ppm every year [8][9][10][11][12]. Workplace Exposure Limits (WELs) apply to healthy people who are at working age and directly exposed to pollutants at their workplaces.…”
Section: Criteria For Workplace Indoor Air Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The inhalation exposure to non-carcinogenic and carcinogenic VOCs has followed the conventional approaches proposed by U.S. EPA (U.S. EPA, 2009b) and previous studies (Al-Zboon and Forton, 2019;Ari et al, 2020;El-Hashemy and Ali, 2018;Kitwattanavong et al, 2013;Loonsamrong et al, 2015;Xing et al, 2018 Non-carcinogenic risk assessment for the mixture of VOCs species was determined as the Hazard Index (HI), which is defined as follows:…”
Section: Quantitative Risk Assessmentmentioning
confidence: 99%
“…Measurements and analysis within the study conducted by Abdullah et al [7], which refers to IAQ a refinery industry, included both PM 2.5 and PM 10 . The conclusion of research concerning IAQ in steel rolling industry, performed by Al-Zboon et al [8], is that PM 10 and PM 2.5 exceeded the international standards at most of the measuring points. Furthermore, within the study related to IAQ in steel making industry, Al-Zboon and Forton [9] reported extremely high concentrations of PM 10 and PM 2.5 in the indoor air.…”
Section: Introductionmentioning
confidence: 97%